Do 'environmental bads' such as alcohol, fast food, tobacco, and gambling outlets cluster and co-locate in more deprived areas in Glasgow City, Scotland?. (May 2018) - Macdonald, Laura; Olsen, Jonathan R.; Shortt, Niamh K.; Ellaway, Anne
Abstract: This study utilised an innovative application of spatial cluster analysis to examine the socio-spatial patterning of outlets selling potentially health-damaging goods/services, such as alcohol, fast food, tobacco and gambling, within Glasgow City, Scotland. For all categories of outlets combined, numbers of clusters increased linearly from the least to the most income deprived areas (i.e. one cluster within the least deprived quintile to ten within the most deprived quintile). Co-location of individual types of outlets (alcohol, fast food, tobacco and gambling) within similar geographical areas was also evident. This type of research could influence interventions to tackle the co-occurrence of unhealthy behaviours and contribute to policies tackling higher numbers of 'environmental bads' within deprived areas. Highlights: For all outlets combined, cluster numbers increased with increasing deprivation. Poorer areas showed more alcohol, fast food, tobacco, and gambling outlet clusters. Our evidence suggested co-location of various types of outlets in similar areas. Cluster analysis was used as an innovative tool to explore spatial retail access.